“Prepare Your Physical Health”: Psikoedukasi Membangun Kesiapan Fisik dan Kesehatan Jelang Pernikahan - Wahyuni, Lussy Dwiutami; Ariyani, Mira; Putri, Fildzah Rudyah; Izzati, Adzkia Zahra; Luthfiyah, Syifa Ananda (Jendela Akademika, 2024)
Pasirtanjung Village is one of the villages in Tanjungsari District, Bogor Regency. The high gap between job seekers and the availability of job opportunities which has an impact on the income they earn is one of the problems in this village. Meanwhile, income is one of the factors that has an impact on a person's readiness to live married life. In addition, people in this village still have the opinion that someone must get married immediately, without paying attention to the individual's readiness, especially in terms of physical and health. For this reason, the Faculty of Psychology, Universitas Negeri Jakarta offers a solution by holding psychoeducation with the theme "Building Physical and Health Readiness Before Marriage". In this activity, people were given counseling, infographics and discussions to identify themselves and build readiness before getting married. The results obtained are that the people of Pasirtanjung Village are more aware of how to prepare themselves before getting married. They are also aware of the impact that will happen on them as a partners and their children in the future if they do not prepare their physical health before carrying out the wedding.